Nestmate Copulation in the Neotropical Eusocial Wasp Polistes Instabilis de Saussure (Hymenoptera: Vespidae) - Sean O'Donnell (Psyche: A Journal of Entomology)
Copulation between individually marked nestmates of the Neotropical eusocial wasp Polistes instabilis is reported. Polistes copulations are rarely observed in the field; this observation is the first documented case of nestmate copulation in the genus. Hamilton (1964) predicted high rates of nestmate copulation for tropical Polistes populations which have asynchronous colony cycles relative to temperate populations. Nestmate copulation may lead to relatively high levels of inbreeding in tropical Polistes species.